Evaluation of a limited area model for short range Prediction over Indian region: Sensitivity studies - MOHANTY, U.C.; PALIWAL, R. K.; TYAGI , AJIT; JOHN, A. (MAUSAM, 1990)
A number or numerical experiments have been performed to study the impact of resolution, lateral boundary conditions and cumulus parameterization scheme on the performance of a multi-level primitive equation limited area, a model for short range predictions over Indian region. The study shows that a limited area model with higher resolution, tendency modification lateral boundary conditions and deep cumulus parameterization based upon modified Kuo scheme as tuned to Indian monsoon conditions leads to better simulation or monsoon circulation. In particulars, a considerable Improvement in the rainfall, intensity and track or monsoon depression is observed.